-9=7p-15-6p

Simple and best practice solution for -9=7p-15-6p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9=7p-15-6p equation:


Simplifying
-9 = 7p + -15 + -6p

Reorder the terms:
-9 = -15 + 7p + -6p

Combine like terms: 7p + -6p = 1p
-9 = -15 + 1p

Solving
-9 = -15 + 1p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-1p' to each side of the equation.
-9 + -1p = -15 + 1p + -1p

Combine like terms: 1p + -1p = 0
-9 + -1p = -15 + 0
-9 + -1p = -15

Add '9' to each side of the equation.
-9 + 9 + -1p = -15 + 9

Combine like terms: -9 + 9 = 0
0 + -1p = -15 + 9
-1p = -15 + 9

Combine like terms: -15 + 9 = -6
-1p = -6

Divide each side by '-1'.
p = 6

Simplifying
p = 6

See similar equations:

| 12xy^2+1=0 | | 24=5X-7 | | 3=3p-4-2p | | 17+9s=2(8s-3) | | 30-5(p-10)=11 | | 16x^2+3=-16x | | -14=4p+7-3p | | 6x+10=2y+10 | | -14=-8p+5+9p | | (x+1)/(2-x)*(2-x)^2/(x-2)*2/x+1 | | -11w+6=-38 | | .24.14= | | 10=-2p-2+3p | | -4=-4p-11+5p | | M/-16=-9 | | y-9=15(x-5) | | 13=3p-15-2p | | x^2+24x-23=0 | | 8x^2-28x+98=0 | | 8x^2-28+98=0 | | 38x-14=20 | | 2(x-2)=-3x+21 | | 2+3.8= | | 3(2a-4)= | | 2(x-2)=-3+21 | | 3a+50=140 | | -9-6=8+x | | (y^2-7)(5y^2-5y+6)= | | 2+38= | | -13=7p-12-6p | | 36r^9-9r^6+54r^3= | | 7(3x-4)=17x |

Equations solver categories